1995
DOI: 10.1089/dna.1995.14.991
|View full text |Cite
|
Sign up to set email alerts
|

Transcription of the 5′-Terminal Cap Nucleotide by RNA-Dependent DNA Polymerase: Possible Involvement in Retroviral Reverse Transcription

Abstract: The possible transcription of the 5'-terminal cap nucleotide of mRNA by RNA-dependent DNA polymerase was examined by a single-step assay, based on the generation of a hairpin structure during reverse transcription of globin mRNA. Using this approach, we demonstrated that the 5'-terminal cap nucleotide of mRNA is indeed transcribed by RNA-dependent DNA polymerase into a 3'-terminal residue of cDNA and were able to measure the extent of such transcription. The observed transcription of the cap nucleotide raises … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
14
0

Year Published

1996
1996
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 15 publications
4
14
0
Order By: Relevance
“…Retroviral RT has previously been reported to reverse-transcribe the cap (Hirzmann et al 1993;Volloch et al 1995). We also present evidence for reverse transcription of a cap in L1-mediated retrotransposition, of processed pseudogenes from the HERV-W family of human endogenous retroviruses (Costas 2002;Pavlicek et al 2002a).…”
Section: Genome Research 2257supporting
confidence: 67%
See 1 more Smart Citation
“…Retroviral RT has previously been reported to reverse-transcribe the cap (Hirzmann et al 1993;Volloch et al 1995). We also present evidence for reverse transcription of a cap in L1-mediated retrotransposition, of processed pseudogenes from the HERV-W family of human endogenous retroviruses (Costas 2002;Pavlicek et al 2002a).…”
Section: Genome Research 2257supporting
confidence: 67%
“…Basically, the cap is a modified GTP. It is known that retroviral reverse transcriptases can reverse-transcribe the cap structure (Hirzmann et al 1993;Volloch et al 1995). As L1 RNA is most likely transcribed by RNA Polymerase II , a cap structure is very likely added to the L1 RNA 5Ј-end.…”
Section: Variable Transcriptional Start Sites In Human L1 Elementsmentioning
confidence: 99%
“…Finally, it has recently been suggested that the 5Ј cap structure of mRNA may have contributed to the proliferation of retrotransposons in eukaryotes (36). Various RTs have been shown to copy the G residue of the 5Ј cap (37,38), which may explain the variable number of G residues found at the 5Ј junction of some elements (36). Our data suggest that these 5Ј caps would also not inhibit end-to-end jumps.…”
Section: Discussionmentioning
confidence: 62%
“…Finally, the sequence of the human L1 element provides presumptive evidence for capping. Previous in vitro studies have shown that various RTs can readily copy the G residue comprising the cap, in spite of its unusual 5Ј-5Ј triphosphate linkage to the mRNA (Hirzmann et al 1993;Volloch et al 1995;Mules et al 1998a). The L1 sequence starts with a run of a variable number G residues, which I propose has accumulated through multiple rounds of cap reverse transcription.…”
Section: Figurementioning
confidence: 99%